Dielectric elastomers based on silicones filled with transitional metal complexes. (15th May 2016) - Ştiubianu, George; Soroceanu, Alina; Varganici, Cristian-Dragos; Tugui, Codrin; Cazacu, Maria
Abstract: New composite dielectric elastomers with improved dielectric properties were prepared on the basis of polydimethylsiloxane rubber filled with new types of metal (Mn, Fe, Cr) complexes of the bis-azomethine derived from the condensation of a siloxane diamine, 1, 3-bis(aminopropyl)tetramethyldisiloxane, with 3, 5-di-bromo-2-hydroxybenzaldehyde. The tetramethyldisiloxane fragment from the structure of the complexes creates the premise for a good compatibility with the silicone matrix without the need for other surface treatments while the complexed metal unit through its polar character changes the dielectric properties of the material. The resulted composites crosslinked at room temperature as dielectric elastomer films were investigated in order to establish if such materials are suitable for use in the structure of electromechanical devices. The introduction of metal complexes in the polymer matrix has led to a slight decrease of the elastic domain but increased the relative dielectric permittivity with up to 100% and the electromechanical sensitivity of the materials, with negligeable changes of the thermal behavior and overall moisture sorption capacity, thus preserving the chemical stability and hydrophobic character of siloxanes.